PENERAPAN MODEL KOOPERATIF TIPE TGT DENGAN MEDIA VISUAL DALAM PENINGKATAN PEMBELAJARAN IPS DI KELAS IV SEKOLAH DASAR - PRATIWI, IKA WINDY (KALAM CENDEKIA PGSD KEBUMEN, 2014)
Abstract: Application of cooperative model TGT type with visual media in increase social studies learning in fourth grade elementary school. This study aimed to describe (1) to describe applied of cooperative models TGT type with visual media increase social studie learning in fourth grade of elementary school, (2) to describe abstacles and solutions in application of cooperative models TGT type with visual media in social studie learning in fourth grade of elementary school. This study is a collaborative classroom action research conducted in two cycles, each cycle consists of planning, acting, observing, reflecting. The result showed that (1) applied of cooperative models TGT type with visual media can be run according to the scenario, can to increase social studies learning in fourth grade of elmentary school. In pre-action mastery percentage is 57% of students, after action performed in first cycle percentage is 81%, and in second cycle percentage is 86%. (2) there are abstacles and found the solutions to applied this model. Keyword: cooperative TGT type, visual media, social studies learning. Abstrak: Penerapan Model Kooperatif Tipe TGT dengan Media Visual dalam Peningkatan Pembelajaran IPS di Kelas IV Sekolah Dasar. Penelitian ini bertujuan mendeskripsikan (1) Mendeskripsikan penerapan model kooperatif tipe TGT dengan media visual yang dapat meningkatkan pembelajaran IPS di kelas IV sekolah dasar, (2) mendeskripsikan kendala dan solusi dalam penerapan model kooperatif tipe TGT dengan media visual melalui pembelajaran IPS di kelas IV sekolah dasar. Penelitian ini adalah penelitian tindakan kelas kolaboratif yang dilaksanakan dalam dua siklus yang mencakup tahap perencanaan, pelaksanaan, observasi dan refleksi. Hasil penelitian menunjukkan: (1) penerapan model kooperatif tipe TGT dengan media visual sesuai skenario dapat meningkatkan pembelajaran IPS kelas IV sekolah dasar. Persentase ketuntasan pra-tindakan mencapai 57%, setelah tindakan siklus I persentase ketuntasan mencapai 81%, siklus II mencapai 86%. (2) penerapan model tersebut terdapat kendala dan telah ditemukan solusi untuk mengatasinya. Kata Kunci: kooperatif tipe TGT, media visual, pembelajaran IPS.